PENGEMBANGAN SOAL HOTS BERBASIS EKOPEDAGOGIK PADA PEMBELAJARAN IPA SD TEMA 5 EKOSISTEM - Dini Nureani Novianti, - (2021)
Education is the process of changing the attitudes and behavior of a person or group of people in an effort to mature humans through teaching or learning efforts. HOTS-oriented learning tools are also effective in increasing the percentage of students' classical learning completeness. HOTS shows that HOTS-oriented Eco pedagogic HOTS questions can improve student learning outcomes. This Eco pedagogy is part of critical pedagogy (educational science) as a form of critical and concern for human social conditions, without a good relationship with nature, humans cannot live comfortably. The objectives of this study are: 1) To describe the development of Eco pedagogic-based HOTS questions in the 5th ecosystem theme of elementary science learning. 2) Describe the feasibility test (teachers, students, material experts and evaluation experts) for the development of Eco pedagogic-based HOTS questions in the ecosystem theme 5 elementary science learning. The type of research used is Research and Development (R&D) which is carried out on the thematic Eco pedagogic HOTS questions based on project based learning using the Borg & Gall model. The population in this study were fifth grade students at SDN Karyamukti 1, Panyingkiran District, Majalengka Regency. Data analysis includes qualitative and quantitative descriptive data analysis techniques.-----Pendidikan merupakan proses pengubahan sikap dan perilaku seseorang atau kelompok orang dalam usaha mendewasakan manusia melalui upaya pengajaran atau pembelajaran. Perangkat pembelajaran berorientasi HOTS juga efektif untuk meningkatkan persentase ketuntasan belajar klasikal siswa. HOTS menunjukkan bahwa soal HOTS ekopedagik yang berorientasi pada HOTS dapat meningkatkan hasil belajar siswa. Ekopedagogik ini menjadi bagian dari pedagogik (ilmu pendidikan) kritis sebagai bentuk kritis dan kepedulian terhadap keadaan sosial manusia, tanpa hubungan baik dengan alam manusia tidak mungkin bisa hidup dengan nyaman. Tujuan penelitian ini adalah: 1) Mendeskripsikan pengembangan soal HOTS berbasis ekopedagogik pada pembelajaran IPA SD tema 5 ekosistem. 2) Mendeskripsikan uji kelayakan (guru, siswa, ahli materi dan ahli evaluasi) pengembangan soal HOTS berbasis ekopedagogik pada pembelajaran IPA SD tema 5 ekosistem. Jenis penelitian yang digunakan adalah Research and Development (R&D) yang dilakukan pada soal HOTS ekopedagik tematik berbasis project based learning ini dengan menggunakan model Borg & Gall. Populasi dalam penelitian ini adalah siswa Kelas V di SDN Karyamukti 1 Kecamatan Panyingkiran Kabupaten Majalengka. Analisis data meliputi teknik analisis data deskriptif kualitatif dan kuantitatif.